Delay-Driven Routing for Low-Duty-Cycle Sensor Networks - Zuzhi Fan (International Journal of Distributed Sensor Networks, 2013)
Duty-cycled operation has been introduced as an efficient way to preserve nodes energy and prolong network lifetime for wireless sensor networks. However, such networks are often logically disconnected since there is a limited number of active nodes within a period of time. Traditional routing algorithms, which have been designed for always-awake wireless networks, suffer excessive waiting time incurred by asynchronous schedule of nodes and cannot be applied to these time-dependent sensor networks. In this work, we study the optimization of delivery delay for low-duty-cycle sensor networks. Specially, we theoretically analyze the sleep latency in low-duty-cycle networks and present a new routing metric, which takes both lossy link and asynchronous schedule of nodes into consideration. Based on the metric, we propose delay-driven routing algorithms to find optimal forwarder in order to reduce delivery delay for source-to-sink communication. We compare our design against state-of-the-art routing algorithms derived in wireless networks through large-scale simulations and testbed experiments, which show that our algorithms can achieve a significant reduction in delivery delay.